(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Institutions must provide recognition systems that are not only technically interoperable and aligned with learner realities. At IHE Delft Institute for Water Education, we are rebuilding our professional practice platform as the IHE Delft LifeLong Learning (LLL) Hub. This relaunch presents an opportunity to embed flexible, verifiable recognition that occurs across diverse contexts—from classrooms and fieldwork to professional settings. In this 20-minute session, members of the Learning Team at IHE Delft—educators, practitioners, and technologists—modeled a participatory approach to future-proofing learning development and recognition. Our goals were twofold: To share lessons learned from our relaunch, and To gather critical feedback from the ePIC community on how to scale and sustain inclusive recognition initiatives across institutional and geographic boundaries. In the first half of the session, we addressed the guiding question: How can we scale up and sustain inclusive development and recognition initiatives? We presented the relaunch of our professional practice development platform and our integration of SURF’s EDUBadge system. While this may appear to be a technical enhancement, it enables transparent recognition workflows and supports learner mobility across contexts. By embedding open credentials on a platform that meets learners where they are, we respond directly to ePIC 2025’s call to "unleash the potential of technology for recognition." In the second half of the session, we returned to the same guiding question—but invited attendees’ responses. Using facilitated prompts, we crowdsourced feedback on: Design principles that support access, choice, and recognition of diverse learner pathways Strategies for long-term sustainability, including institutional alignment, cross-sector partnerships, and policy enablers Throughout the session, we shared design principles for building resiliency into LLL Hub administration. These include: Acknowledging the limitations many of our (primarily Global South) learners face (e.g., connectivity, time constraints, language barriers Supporting autonomous, non-linear learner journeys Ensuring transparency in how recognition is awarded, interpreted, and shared Our approach draws upon key European and international framework recommendations that advocate for learner-centered, interoperable recognition systems: The (2020) European Commission’s roadmap for micro-credentials, SURF’s EDUBadges (2022) implementation report, which offers a scalable national infrastructure for open recognition in Dutch higher education, and UNESCO’s (2023) report on digital credentialing for inclusive and equitable learning. By presenting the early stage of the relaunch as a living case study, we showed how these design principles are enacted in practice. We argued that this approach offers a realistic and transferable model for institutions seeking to move beyond pilots toward sustainable recognition ecosystems. Participants gained insights into how cross-functional collaboration, thoughtful platform design, and tools like EDUBadges can support this transformation. Ultimately, this session invited the ePIC community to co-create futures in which learners are truly seen, valued, and supported across the full arc of their learning journeys. Keywords: lifelong learning, professional practice, recognition systems, open credentials, inclusive recognition